Method for layer-by-layer deposition of concrete using rapidly hydrated cementitious material and two-component cementitious binder composition therefor

By hybrid concrete base adhesives and dual -component cement binder compositions of the carrier material, it is difficult for the concrete in the existing technology to meet the high liquidity and high construction requirements at the same time during the pumping and sedimentary stage. The problem achieves efficient 3D printing effects and environmental performance.

CN119384342APending Publication Date: 2025-01-28UNIV GENT
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380042667.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-30
Filing Date
2023-05-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to meet the high flowability and high constructability requirements of concrete at the pumping and deposition stages, especially in 3D printing applications, resulting in deformation and collapse problems during the extrusion process.

Method used

通过混合缓凝水泥基粘合剂和载体材料组成的双组分水泥基粘合剂组合物,利用缓凝剂延长水泥基粘合剂的初始凝结时间,并通过调整pH值和粘度比率,实现高流动性和高可建造性的可挤出混凝土。

Benefits of technology

It realizes that before the extrusion is high and low -liquidity after extrusion, the high -demand can be squeezed out of the concrete, which meets the high requirements such as 3D printing, avoids the problems of deformation and collapse. Tram cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384342A_ABST
    Figure CN119384342A_ABST
Patent Text Reader

Abstract

The invention relates to a method for the layer-by-layer deposition of concrete, in particular of concrete using a rapidly hydrated cementitious binder. The first stream and the second stream are provided to a mixer (D) to obtain extrudable concrete. The pH of the second stream is greater than the pH of the first stream, the pH difference being at least 2. The first stream comprises a retarded cementitious binder obtainable by mixing a cementitious binder (i.e., calcium sulphoaluminate and / or calcium aluminate) with a retarder comprising a compound comprising boron and sodium. The retarder allows for an increase in setting time of the cementitious binder and allows for the pH of the first stream to be affected in such a way that the pH of the first stream is lower than the pH of a stream equal to the first stream but containing the cementitious binder rather than the retarded cementitious binder. The second stream comprises a carrier material. The volume fraction of the carrier material is at least 20% by volume of the second flow. The invention also relates to a two-component cementitious adhesive composition for use in the aforementioned process.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to a method for depositing concrete layer by layer by providing an extrudable concrete having high fluidity (high pumpability) before extrusion and low fluidity (high buildability) after extrusion. In particular, the present invention relates to a method for depositing concrete layer by layer using a fast hydrating cement-based binder such as calcium sulphoaluminate cement or calcium aluminate cement.

[0002] The present invention also relates to a two-component cementitious adhesive composition comprising a first component containing a fast-hydrating cementitious material such as calcium sulfoaluminate cement or calcium aluminate cement. Background Art

[0003] Concrete is a widely used building material. In recent decades, pumping has become an indispensable technology for pouring fresh concrete. Pumping fresh concrete remains challenging due to conflicting requirements for fresh concrete during the pumping process, which requires high fluidity, and during the post-pumping process, which requires high buildability.

[0004] On the one hand, good fluidity maintenance is required to obtain good concrete pumpability. In case of (brief) interruptions, such as those caused by delays in material feeding, good fluidity maintenance is beneficial for reducing the pumping pressure and resuming the pumping operation. On the other hand, excellent buildability should be achieved both in formwork casting and in formwork-free construction methods. Buildability is defined as the ability of a material to retain its shape without flowing once it has been extruded (e.g. printed). In formwork casting, good buildability is required to avoid formwork leakage or excessive formwork pressure during casting. This requirement is even more challenging in construction methods without formwork (e.g. extrusion-based 3D concrete printing) to avoid deformation or collapse of the extruded material.

[0005] Obviously, the requirements for high flowability and good buildability are contradictory. This contradiction remains one of the biggest challenges for extruded concrete, especially for 3D printing of concrete.

[0006] In order to obtain the desired fluidity and buildability of concrete, several types of Portland-based cement mixtures have been proposed. Such cement mixtures contain accelerators, such as aluminum sulfate, to achieve rapid hardening after the pumping stage. However, Portland-based cement mixtures have some disadvantages. In cases where accelerators (such as aluminum sulfate) are not mixed, durability problems (due to internal sulfate attack) may occur. In addition, such mixtures require very high binder contents and may suffer from significant shrinkage problems and cracking. In addition, due to the high dosage of Portland cement (PC), such mixtures have a high CO2 footprint.

[0007] In order to make a more durable mix, mixes have been proposed in which the Portland cement (PC) is partially replaced by calcium sulfoaluminate (CSA) cement. CSA cement has a much lower CO2 footprint compared to PC cement, as CSA cement produces much lower CO2 emissions (about 50%) compared to PC cement.

[0008] One of the major bottlenecks of CSA-based mixes is their significantly shorter open time compared to PC cement. This is mainly due to the very short induction period caused by the rapid hydration of CSA cement. Therefore, CSA cement requires a suitable retarder to extend the open time of CSA-based mixes to the required level. Different retarders have been proposed to extend the open time of CSA-based mixes. Examples of retarders include sodium gluconate, borax, and citric acid. Mohan et al. (MK Mohan, AVRahul, G. De Schutter, K. Van Tittelboom, Early age hydration, rheology and pumping characteristics of CSA cement-based 3D printable concrete (Early hydration, rheology and pumping characteristics of CSA cement-based 3D printable concrete), Constr. Build. Mater. 275 (2021) 122136) explored the feasibility of using borax (disodium tetraborate decahydrate, NaBa4O7.10H2O) as a retarder in CSA-based mixes for layer-by-layer deposition applications.

[0009] However, the layer-by-layer deposition of such slow-setting CSA-based mixes remains challenging due to the conflicting requirements for high flowability and good buildability during the pumping and deposition stages.

[0010] Recently, methods have been proposed for adding a (liquid) accelerator to an extrudable material at a nozzle. WO2021 / 214239 describes a method for layer-by-layer deposition of concrete, wherein a first stream comprising a binder material and a second stream comprising an accelerator are mixed in a static mixer to provide an extrudable concrete. Although this method shows positive results using Portland-based cement as a first-stream binder material, the two-phase mixing process using fast-hydrating cements (such as CSA-based cements) remains complicated. As mentioned above, CSA-based cements require suitable retarders, and layer-by-layer deposition of such retarded CSA-based cements remains challenging.

[0011] CN 105384416 describes a two-component cement system, wherein the first component comprises aluminum sulfate cement and a retarder, the retarder comprising a mixture of sodium tetraborate, sodium gluconate and tartaric acid, and wherein the second component comprises an aqueous mixture (91.5-94% mixed water) containing lithium carbonate as an accelerator. The disadvantage of this system is the use of a mixture of multiple retarders, each of which may have a negative impact on the final properties of the final product. In addition, the second component comprises an aqueous mixture (91.5-94% mixed water) and therefore has a low viscosity (close to 1 mPa). Due to the significant difference in viscosity between the first and second materials, the first material will produce a laminar flow, while the flow of the second material is turbulent. Therefore, using this two-component system will not be able to achieve a uniform mixing of the components in the deposition material. SUMMARY OF THE INVENTION

[0013] It is an object of the present invention to provide a method of providing an extrudable concrete which avoids the problems of the prior art.

[0014] Another object of the present invention is to provide a method for depositing concrete layer by layer using fast hydrating cementitious materials.

[0015] It is a further object of the present invention to provide an extrudable concrete having sufficiently high flowability to allow pumping and high buildability to allow the forming of structures, in particular 3D printed structures.

[0016] Another object of the present invention is to provide an extrudable concrete suitable for layer-by-layer deposition at high printing speeds.

[0017] Another object of the present invention is to provide an extrudable concrete by mixing a first stream and a second stream, thereby obtaining excellent mixing uniformity of the first stream and the second stream.

[0018] Another object of the present invention is to provide a method for providing extrudable concrete containing no Portland cement or containing a low percentage of Portland cement.

[0019] Another object of the present invention is to provide a method of providing an extrudable concrete having high mechanical integrity, having a lower CO2 footprint compared to Portland based compositions, not suffering from shrinkage and requiring no shrinkage reducers or shrinkage compensators.

[0020] It is yet another object of the present invention to provide a method of providing an extrudable concrete having low porosity and a dense microstructure.

[0021] Yet another object of the present invention is to provide an extrudable concrete for layer-by-layer deposition which does not require accelerators such as sulfates (e.g., sodium sulfate, magnesium sulfate, potassium sulfate, lithium sulfate, or aluminum sulfate) and carbonates (e.g., sodium carbonate, magnesium carbonate, potassium carbonate, or lithium carbonate) and therefore does not suffer from internal sulfate attack nor from durability problems caused by such accelerators.

[0022] Still another object of the present invention is to provide a two-component cementitious adhesive composition suitable for layer-by-layer deposition, the two-component cementitious adhesive composition comprising a fast-hydrating cementitious material as a first component.

[0023] According to a first aspect of the present invention, there is provided a method for depositing concrete layer by layer by providing extrudable concrete, and preferably continuously providing extrudable concrete. The method comprises the following steps:

[0024] - The first and second streams are fed to a mixer, preferably the first and second streams are pumped to the mixer.

[0025] The first stream has a first pH (pH 1) and comprises a first material and optionally water. The first material comprises a slow-setting cement-based binder, preferably a slow-setting fast-hydrating cement-based binder. The slow-setting cement-based binder can be obtained by mixing a cement-based binder with a retarder. The cement-based binder has an initial setting time T cem , and the slow-setting cement-based adhesive has an initial setting time T ret cem .

[0026] The cement-based binder preferably comprises a fast hydrating cement-based binder.Preferred cement-based binders are binders selected from the group consisting of calcium sulphoaluminate and calcium aluminate or a combination thereof.

[0027] The retarder comprises a compound that, when mixed with the cement-based binder to provide the retarded cement-based binder, can affect the initial setting time, such that the initial setting time T of the retarded cement-based binder is ret cem Higher than the initial setting time T of the cement-based adhesive cem , and the retarder is capable of affecting the pH of the first stream in the following manner: making the first pH (pH1) of the first stream (comprising the retarding cementitious binder) lower than or equal to the pH of a stream of the first stream but comprising the cementitious binder instead of the retarding cementitious binder and not comprising the retarder. The retarder comprises a compound containing boron and sodium. A preferred retarder comprises borax (disodium tetraborate decahydrate, NaBa4O7.10H2O).

[0028] The second stream has a second pH (pH2) and comprises a second material and optionally water. The second material has a second initial coagulation time T2.

[0029] The second pH (pH 2) is greater than the first pH (pH 1), and the difference between the first pH (pH 1) and the second pH (pH 2) is at least 2, such as 3 or 4.

[0030] The second material comprises a support material, preferably a powdered support material. The volume fraction of the support material is at least 20% by volume of the second stream, preferably at least 20% by volume of the second material.

[0031] The second material may further comprise a pH modifier. A pH modifier may be added to achieve the second pH (pH 2) requirement. In a preferred embodiment, the second material comprises a carrier material and a pH modifier.

[0032] The second material comprising the carrier material or comprising the carrier material and at least one pH modifier may also comprise a binder material and / or an aggregate material and / or a supplementary cementitious material and / or one or more additional compounds.

[0033] - mixing the first stream and the second stream in a mixer to obtain a third stream comprising extrudable concrete. The third stream comprises a mixture of the first material, the second material and optionally water. The mixture of the first material and the second material has an initial setting time T3, wherein the initial setting time T3 is less than the initial setting time T3 of the slow setting cement-based binder. ret cem In a preferred embodiment, the initial setting time T3 is also less than the initial setting time T of the cement-based adhesive. cem .

[0034] As mentioned above, the slow-setting cementitious binder can be obtained by mixing a cementitious binder, preferably a fast-hydrating cementitious binder, with a retarder. The cementitious binder is preferably a non-slow-setting cementitious binder.

[0035] The initial setting time of cement-based adhesives is called T cem The initial setting time of the mixture, i.e. the slow setting cement-based binder, is called T ret cem .

[0036] By mixing the cement-based binder with the retarder, the initial setting time of the obtained mixture, i.e. the retarded cement-based binder, is prolonged. This means that T ret cem Larger, preferably significantly larger than T cem In this way, a slow-setting or dormant cementitious binder is obtained, thereby obtaining a slow-setting or dormant first material.

[0037] The term "initial setting time", also known as "initial setting time" or "initial open time", refers to the time that elapses from the moment water (or alkali-activated solution) is added to the material or material mixture to the moment the paste begins to lose its plasticity. For the purposes of the present invention, the initial setting time is determined by the penetration resistance method. The initial setting time refers to the time from the moment water (or alkali-activated solution) is added to the material or material mixture until the formed material reaches 3.5 N / mm 2 The time period it takes to penetrate the resistance.

[0038] Initial setting time T of cement-based adhesive cem is the time from when water (or alkali activated solution) is added to the cementitious binder (i.e. the cementitious binder which is not mixed and not in contact with the retarder) until the formed material reaches 3.5 N / mm 2 For mixing the materials, a standard rotary mixer is preferably used.

[0039] The cement-based binder preferably comprises a fast hydrating cement-based binder, preferably with an initial setting time T cem Cement-based adhesives with an initial setting time of less than 30 minutes, such as cem Cement-based adhesives with an initial setting time of less than 20 minutes, such as cem Range between 10 minutes and 20 minutes for cement-based adhesives.

[0040] Initial setting time T of slow-setting cement-based adhesive ret cem The value is the time from the time when water (or alkali-activated solution) is added to a retarding cementitious binder (i.e., a binder obtainable by mixing a cementitious binder (i.e., a non-retarding cementitious binder that is not mixed and not in contact with a retarder) and a retarder) to the time when the formed material reaches 3.5 N / mm 2 For mixing the materials, a standard rotary mixer is preferably used.

[0041] The slow-setting cement-based adhesive preferably has an initial setting time T greater than 30 minutes, such as greater than 60 minutes, 90 minutes or 120 minutes. ret cem Preferably, the initial setting time T of the retarder cement-based adhesive is ret cem Between 60 and 180 minutes.

[0042] The second initial coagulation time T2 is from the time when water (or alkali activation solution) is added to the second material of the second stream to the time when the formed material reaches 3.5 N / mm 2For mixing the materials, a standard rotary mixer is preferably used.

[0043] The initial setting time T2 is greater than the initial setting time T of the cement-based adhesive. cem Preferably, the initial setting time is greater than the initial setting time T of the slow setting cement-based adhesive. ret cem More preferably, the initial setting time T2 is significantly greater than the initial setting time T of the cement-based adhesive. ret cem For example, the initial coagulation time T2 is the initial coagulation time T ret cem In a preferred embodiment, the initial coagulation time T2 is the initial coagulation time T ret cem In a specific embodiment, the initial coagulation time T2 is the initial coagulation time T ret cem At least 20 times of the initial setting time T ret cem At least 40 times.

[0044] Preferably, the initial setting time T2 is at least 30 minutes. More preferably, the initial setting time T2 is at least 120 minutes, and even more preferably, the initial setting time T2 is at least 180 minutes, at least 240 minutes, at least 300 minutes, at least 360 minutes, at least 420 minutes or at least 480 minutes.

[0045] The third initial coagulation time T3 is from the moment when water (or an alkali activation solution) is added to the mixture of the first material of the first stream and the second material of the second stream to the moment when the formed material reaches 3.5 N / mm 2 For mixing the materials, a standard rotary mixer is preferably used.

[0046] The initial setting time T3 is less than the initial setting time T of the slow setting cement-based adhesive. ret cem .

[0047] In a preferred embodiment, the initial setting time T3 is also less than the initial setting time T of the cement-based adhesive. cem In a particular embodiment, the initial setting time T3 is less than the initial setting time T of the cement-based adhesive. cem One quarter or one tenth of .

[0048] Preferably, the initial setting time T3 ranges between 1 and 15 minutes, and more preferably, the initial setting time T3 ranges between 1 and 5 minutes.

[0049] Surprisingly, it has been found that by retarding cementitious materials, in particular rapidly hydrating cementitious materials, with a retarder according to the invention, and by combining a first stream comprising a retarded cement with a second stream having a pH significantly higher than that of the first stream, the retarded cementitious binder can be reactivated and the hydration of the retarded cementitious binder can be restarted, thereby allowing layer-by-layer deposition, in particular at high printing speeds. The method according to the invention allows obtaining printing speeds higher than 500 mm / sec, for example 700 mm / sec, 800 mm / sec, 900 mm / sec or 1000 mm / sec.

[0050] The process according to the invention does not require the presence of carbonates (e.g. sodium carbonate, magnesium carbonate, potassium carbonate or lithium carbonate) and sulfates (e.g. sodium sulfate, magnesium sulfate, potassium sulfate or lithium sulfate) in the first or second stream. This is an important advantage over the systems known in the prior art which use, for example, lithium carbonate, since the presence of such compounds may reduce the mechanical strength at a later stage.

[0051] Preferably, the first stream and the second stream are free of carbonates and sulphates.

[0052] As mentioned above, the first stream has a first pH, which is referred to as pH 1. Preferably, the first stream has a first pH ranging between 7 and 10 (pH 1).

[0053] The first stream comprises the first material and optionally water. Preferably, the first stream comprises the first material and water. The volume fraction of water in the first stream is preferably equal to or lower than 50 volume %, equal to or lower than 40 volume %, equal to or lower than 30 volume %, equal to or lower than 20 volume %, such as 10 volume %, of the first stream. In a preferred embodiment, the volume fraction of water ranges between 10 volume % and 50 volume %, such as between 20 volume % and 50 volume %, of the first stream.

[0054] The first stream can be introduced from a storage container comprising the first material and water. Alternatively, the stream of the first material is transported to a blender and water and / or cementitious binder and / or aggregate material and / or auxiliary cementitious material and / or one or more additional compounds, such as plasticizer or superplasticizer, from a storage container comprising the first material. Optionally, the first stream also comprises one or more (super) plasticizers. For example, before the stream of the first material enters the inlet of the blender (soon), such one or more (super) plasticizers are added to the first material.

[0055] The first material comprises a slow setting cementitious binder and optionally an aggregate material and / or a supplementary cementitious material and / or one or more additional compounds, such as one or more plasticizers and / or one or more superplasticizers.

[0056] The slow-setting cement-based adhesive can be obtained by mixing the cement-based adhesive with a retarder. The cement-based adhesive has an initial setting time T cem , the slow-setting cement-based adhesive has an initial setting time T ret cem , T ret cem Greater than T cem .

[0057] Preferred cement-based binders comprise calcium sulfoaluminate and calcium aluminate or a combination thereof.

[0058] Calcium sulphoaluminate cement is defined as containing ye'elimite (Ca4Al6O 16 Calcium sulfoaluminate cements may also contain dicalcium silicate or C2S and tetracalcium alumina ferrite or C4AF.

[0059] Calcium aluminate cement is defined as a cement comprising mainly hydraulic calcium aluminate, especially calcium monoaluminate (CaAl2O4, CaO·Al2O3).

[0060] With regard to the method according to the invention, the choice of the retarder used to obtain the retarded cementitious binder is crucial. The retarder should allow reactivation of the retarded cementitious binder once the first and second streams are mixed to provide an extrudable concrete and should allow obtaining an extrudable concrete that meets the requirements of having high pumpability and high buildability, making it suitable for layer-by-layer deposition.

[0061] The retarder should allow for an effect on the initial setting time of the cementitious binder so that when mixed with the cementitious binder to provide a retarded cementitious binder, the initial setting time T of the retarded cementitious binder is ret cem Higher than the initial setting time T of cement-based adhesive cem . Furthermore, preferably, the retarder should allow to influence the pH of the first stream in such a way that the first pH (pH1) of the first stream (comprising the retarding cementitious binder) is lower than the pH of a stream equal to the first stream but comprising the cementitious binder instead of the retarding cementitious binder and not comprising the retarder. Preferably, the pH of the first stream (pH1) is at least one unit lower than the pH of a stream equal to the first stream but comprising the cementitious binder instead of the retarding cementitious binder and not comprising the retarder.

[0062] In one embodiment according to the invention, the pH of the first stream comprising the retarding cementitious binder is 9.07, whereas the pH of a stream equal to the first stream but comprising the cementitious binder instead of the retarding cementitious binder and not comprising the retarder is 10.55.

[0063] The retarder used according to the invention comprises a compound containing boron and sodium.

[0064] Preferred compounds containing boron and sodium include borax (disodium tetraborate decahydrate, NaBa4O7.10H2O).

[0065] Aggregate materials include, for example, gravel, crushed stone or sand.

[0066] Supplementary cementitious materials (SCM) include, for example, fly ash, slag (blast furnace slag) and / or silica fume.

[0067] In a preferred embodiment, the first material comprises sand as aggregate material.Preferably, the amount of sand is less than 60% by volume of the material of the first stream or less than 50% by volume of the material of the first stream.

[0068] Preferably, the amount of sand is at least 20% by volume of the material of the first stream, such as at least 30% by volume.

[0069] Preferably, the first material does not comprise Portland cement or alkali activated binder material.Preferably, the first material does not comprise cement based binder present in the second stream.

[0070] The second stream has a second pH, referred to as pH2, and a second initial coagulation time, referred to as T2.

[0071] Preferably, the second pH (pH2) ranges between 10 and 14. As described above, the second pH (pH2) is greater than the pH of the first stream, referred to as the first pH or pH 1. In addition, the difference between the first pH (pH 1) and the second pH (pH 2) is at least 2 units, such as 2.5 units, 3 units, 3.5 units or 4 units.

[0072] In a preferred embodiment, the first pH is equal to 7 and the second pH is equal to 10. In an alternative embodiment, the first pH is equal to 8 and the second pH is equal to 11.

[0073] The second stream comprises a second material and optionally water. Preferably, the second material comprises a second material and water. The volume fraction of water in the second stream is preferably equal to or less than 50% by volume of the second stream, equal to or less than 40% by volume of the second stream, equal to or less than 30% by volume of the second stream, equal to or less than 20% by volume of the second stream, such as 10% by volume of the second stream. In a preferred embodiment, the volume fraction of water ranges between 10% and 50% by volume of the second stream, such as between 20% and 50% by volume of the second stream.

[0074] The second stream may be introduced from a storage container comprising the second material and water. Alternatively, the stream of the second material is conveyed from a storage container comprising the second material to the mixer and water and / or one or more additional compounds such as aggregate material and / or one or more (super) plasticizers are added to the stream of the second material, e.g. shortly before (shortly) the stream of the second material enters the inlet of the mixer.

[0075] The second material comprises a support material. As mentioned above, at least 20% by volume of the second stream, and preferably at least 30%, at least 40% by volume or at least 50% by volume of the second stream comprises a support material.

[0076] More preferably, at least 20 volume % of the second material, at least 30 volume % of the second material, at least 40 volume % of the second material, or at least 50 volume % of the second material comprises the support material.

[0077] In a preferred embodiment, the second material comprises a carrier material and at least one pH modifier. Optionally, the second material comprising a carrier material or a carrier material and at least one pH modifier further comprises one or more binder materials and / or aggregate materials and / or auxiliary cementitious materials and / or one or more additional compounds.

[0078] Preferably, the second material does not include the cement-based binder present in the first stream.

[0079] The support material comprises, for example, limestone, calcium hydroxide and / or sand.

[0080] Preferably, the carrier material or at least a portion of the carrier material comprises a pulverulent carrier material.

[0081] "Powdered material" refers to a material preferably having a particle size of less than 100 μm, less than 80 μm or less than 50 μm. More preferably, the average particle size of the powdered material according to the present invention ranges between 0.1 µm and 100 µm, between 1 µm and 100 µm or between 10 µm and 100 µm. The average particle size of the powdered material according to the present invention ranges, for example, between 0.1 µm and 80 µm, between 0.1 µm and 50 µm, between 0.1 µm and 30 µm, between 0.1 µm and 10 µm or between 1 µm and 10 µm. The average particle size of the powdered material according to the present invention is, for example, 3 µm, 4 µm or 5 µm.

[0082] The particle size (average particle size) may be determined by any method known in the art. A preferred method for determining the particle size (average particle size) includes laser diffraction analysis.

[0083] Preferred powdered carrier materials comprise limestone fillers, such as limestone powder, mineral powders, for example sand or quartz powder, or combinations thereof.

[0084] In order to obtain a flowable and preferably also pumpable mixture, the volume fraction of the pulverulent carrier material is preferably sufficiently high. In a preferred embodiment, the carrier material preferably has a volume fraction of at least 20% of the second material. More preferably, the carrier material has a volume fraction of at least 30% or at least 40% by volume of the second material.

[0085] As pH modifier, there may be considered any compound suitable for influencing the pH of the second stream (pH 2) so that the pH of the second stream is greater than the pH of the first stream (pH 1).

[0086] Preferred pH modifiers include hydroxides such as calcium hydroxide Ca(OH)2, sodium hydroxide NaOH, and potassium hydroxide KOH.

[0087] The pH modifier is present in an amount to obtain the following result: the second pH (pH2), i.e., the pH of the second stream, is higher than the first pH (pH1), i.e., the pH of the first stream, and the difference between the second pH (pH2) and the first pH (pH1) is at least 2 units, for example 2.5 units, 3 units, 3.5 units or 4 units.

[0088] In a preferred embodiment, the second component comprises at least one pH modifier. More preferably, the pH modifier or multiple pH modifiers are present in an amount ranging between 0.1 and 6 wt %, such as in an amount ranging between 0.5 and 5 wt %, such as 1 wt %, 2 wt %, 3 wt % or 4 wt %. In a preferred embodiment, the pH modifier or multiple pH modifiers are present in an amount ranging between 0.1 and 6 wt % of the slow setting cementitious binder of the first component.

[0089] The pH modifier preferably does not include salts of weak acids, such as carbonates (eg, sodium carbonate, sodium bicarbonate, and lithium carbonate), phosphates (eg, sodium phosphate), and salts of carboxylic acids (eg, salts of acetic acid, such as sodium acetate).

[0090] The binder material comprises, for example, a cement-based binder material, an alkali-activated binder material, or a combination of a cement-based binder material and an alkali-activated binder material.

[0091] Where the second stream comprises a binder material, such binder material is preferably present in an amount ranging between 20 and 40 volume % of the second stream, more preferably present in an amount ranging between 25 and 35 volume % of the second material of the second stream.

[0092] The cementitious binder material may comprise any building material that can be mixed with a liquid, such as water, to form a plastic paste.The initial setting time of the binder material of the second material is preferably greater than the initial setting time of the cementitious binder of the first material.

[0093] The cement-based binder material comprises, for example, cement, such as portland cement, lime and calcium sulfoaluminate cement. The cement-based material can also comprise aggregates such as gravel, crushed stone and / or sand. The cement-based material can also comprise reactive and / or non-reactive additives. In addition, the cement-based material can comprise auxiliary cement-based materials (SCM), such as fly ash, slag (blast furnace slag) and / or silica fume. The initial setting time of the cement-based binder of the second material is preferably greater than the initial setting time of the cement-based binder of the first material. Preferred cement-based binders comprise portland cement.

[0094] Alkali activated binder materials, sometimes referred to as geopolymer binder materials, comprise materials with high silica and / or alumina content which form a plastic paste under alkaline conditions (induced by an alkali activator). Alkali activated binder materials may comprise artificial or natural siliceous and / or aluminous materials. Artificial materials include industrial byproducts such as granulated blast furnace slag, granulated phosphorus slag, iron slag and non-ferrous metal slag, coal fly ash, silica fume and calcined products such as metakaolin. Natural materials include volcanic glasses such as volcanic ash, zeolites, siliceous volcanic ash, diatomaceous earth.

[0095] Where the second material comprises aggregate material, the aggregate material may comprise, for example, gravel, crushed stone or sand.

[0096] Where the second material comprises a supplementary cementitious material (SCM), the supplementary cementitious material may comprise fly ash, slag (blast furnace slag) and / or silica fume.

[0097] Where the second stream comprises aggregate material, such aggregate material is preferably present in an amount ranging between 20 and 50% by volume of the second stream, such as between 25 and 45% by volume of the second stream, such as between 30 and 35% by volume of the second stream. More preferably, the aggregate material is present in an amount ranging between 20 and 50% by volume of the second material of the second stream, such as between 25 and 45% by volume of the second material of the second stream, such as between 30 and 35% by volume of the second material of the second stream.

[0098] In a preferred embodiment the second stream comprises sand as aggregate material. Preferably the amount of sand is less than 70% by volume of the material of the second stream, less than 60% by volume of the material of the second stream or less than 50% by volume of the material of the second stream.

[0099] The one or more additional compounds comprise, for example, one or more plasticizers and / or one or more superplasticizers.

[0100] Where the second stream comprises one or more additional compounds, such additional compounds are preferably present in an amount ranging between 10 and 40% by volume of the second stream, such as 20%, 25% or 30% by volume of the second stream. More preferably, the additional compound is present in an amount ranging between 10 and 40% by volume of the second material of the second stream, such as between 20 and 30% by volume of the second material of the second stream.

[0101] In a preferred embodiment of the present invention, the second stream comprises:

[0102] - inert fillers (such as limestone or quartz powder), calcium hydroxide and water;

[0103] - inert fillers (such as limestone or quartz powder), Portland cement and optionally a pH modifier (such as calcium hydroxide or sodium hydroxide);

[0104] - sand, Portland cement, optionally a pH modifier (such as calcium hydroxide or sodium hydroxide) and water;

[0105] - sand, alkali activated mixture, the activated mixture is made with precursors (such as fly ash, ground granulated blast furnace slag, copper slag, steel slag, metakaolin and blends or mixtures thereof) and activator solution (such as sodium hydroxide, sodium silicate, sodium sulfate and blends or mixtures thereof).

[0106] The first and second streams are preferably flowable (= able to flow). More preferably, the first and second streams are flowable and pumpable (= able to be pumped). This means that the flowability and viscosity of the first and second streams should meet certain requirements.

[0107] The fluidity of the first and second streams is preferably high enough. The term "fluidity" refers to the ability of a material to flow. Fluidity can be measured by a flow bench test. The freshly mixed material is placed in two layers in a conical mold. The mold is then removed and the vibrating table is dropped 25 times in 15 seconds. The final diameter represents the fluidity of the fresh material.

[0108] The viscosity of the first stream (referred to as the first viscosity V1) and the viscosity of the second stream (referred to as the second viscosity V2) preferably range between 0.1 Pa.s and 60 Pa.s. More preferably, the first viscosity V1 and / or the second viscosity V2 is at least 1 Pa.s, at least 2 Pa.s, at least 3 Pa.s, at least 4 Pa.s, at least 5 Pa.s or at least 10 Pa.s. For example, the first viscosity V1 and the second viscosity V2 range between 1 Pa.s and 50 Pa.s or between 1 Pa.s and 40 Pa.s.

[0109] The ratio V1 / V2 of the first viscosity V1 to the second viscosity V2 preferably ranges between 1 / 40 and 40. More preferably, the ratio V1 / V2 ranges between 1 / 20 and 20. Even more preferably, the ratio V1 / V2 ranges between 1 / 10 and 10, between 1 / 5 and 5 or between 1 / 2 and 2. In particularly preferred embodiments, the ratio V1 / V2 ranges between 0.7 and 1.3, for example between 0.8 and 1.2 or between 0.9 and 1.1.

[0110] The term "viscosity" refers to the resistance of a fluid to deform at a given shear rate. The viscosity of the first, second and third streams is measured by flow curve tests, usually performed on a rotational rheometer. Most rotational rheometers work according to the Searle principle: an electric motor drives a geometry inside a fixed cup. The rotation speed of the float is preset and generates the motor torque required to rotate the measuring geometry. This torque must overcome the viscous force of the material being measured and is therefore a measure of its viscosity.

[0111] The first flow is supplied to the mixer at a flow rate F1, and the second flow is supplied to the mixer at a flow rate F2. The first flow rate F1 preferably ranges between 0.5 L / min and 100 L / min, such as 1 L / min, 10 L / min, 20 L / min or 50 L / min. The second flow rate preferably ranges between 0.5 L / min and 100 L / min, such as 1 L / min, 10 L / min, 20 L / min or 50 L / min.

[0112] Preferably, the ratio F1 / F2 of flow rate F1 to flow rate F2 ranges between 1 / 10 and 10, more preferably between 1 / 5 and 5 or between 1 / 2 and 2; for example 0.8, 0.9, 1, 1.1 or 1.2.

[0113] The first stream is preferably supplied to the mixer by pumping. For example, the first stream is introduced into the mixer by a first pump pumping the first material and water to the inlet of the mixer. For example, the second stream is introduced into the mixer by a second pump pumping the second material and water to the inlet of the mixer.

[0114] The first pump and the second pump can be started at the same time or not. When the first pump and the second pump are started at the same time, the first pump and the second pump work in the same time interval and start and stop at the same time.

[0115] In a preferred embodiment, the first pump and the second pump are not deactivated at the same time. In a specific embodiment, the second pump or one of the second pumps is deactivated while the other pump is still active. This mode of operation can be preferably used to rinse the mixer once the deposition process stops or is interrupted.

[0116] The first stream is preferably introduced into a first inlet of the mixer and the second stream is preferably introduced into a second inlet of the mixer.

[0117] The first and second streams are supplied to the mixer in a first stream / second stream volume ratio ranging between 10 / 90 and 90 / 10, for example, in a first stream / second stream volume ratio of 20 / 80 or 80 / 20 or in a first stream / second stream volume ratio of 30 / 70 or 70 / 30.

[0118] The third stream comprises a mixture of the first material, the second material and optionally water.Preferably, the third stream comprises a mixture of the first material, the second material and water.

[0119] Optionally, the third stream further comprises one or more additional compounds.

[0120] According to a second aspect of the present invention, a two-component cement-based adhesive composition is provided, the composition comprising a first component and a second component.

[0121] The first component and the second component are preferably in a volume ratio of the first component / the second component between 10 / 90 and 90 / 10. In a preferred embodiment, the volume ratio of the first component / the second component is between 20 / 80 and 80 / 20 or between 30 / 70 and 70 / 30.

[0122] The first component comprises a slow setting cementitious binder, which can be obtained by mixing the first cementitious binder with between 0.1% and 5% by weight of a retarder or a combination of retarders. The first cementitious binder is selected from the group consisting of sulphoaluminate cement, aluminate cement and a combination thereof. The retarder comprises a compound containing boron and sodium. A preferred compound containing boron and sodium comprises borax (disodium tetraborate decahydrate, NaBa4O7.10H2O).

[0123] Optionally, the first component further comprises aggregate material and / or supplementary cementitious material and / or one or more additional compounds.

[0124] Preferably, the first component comprises at least 30 wt% of the slow setting cementitious binder, such as at least 40 wt%, at least 50 wt% or at least 60 wt% of the slow setting cementitious binder.

[0125] As mentioned above, cement-based adhesives have an initial setting time T cem , the slow-setting cement-based adhesive has an initial setting time T ret cem , T ret cem Greater than T cem .

[0126] The second component comprises a support material and an optional pH modifier. The volume fraction of the support material is preferably at least 20% by volume of the second component. More preferably, the volume fraction of the support material is at least 30% by volume, at least 40% by volume or at least 50% by volume of the second component.

[0127] The support material comprises, for example, limestone, calcium hydroxide and / or sand.

[0128] Preferably, the support material or at least a portion of the support material comprises a powdered support material. Preferably, at least 20% by volume of the second component comprises a powdered support material. More preferably, the volume fraction of the powdered support material is at least 30%, at least 40% by volume or at least 50% by volume of the second component.

[0129] "Powdered material" refers to a material preferably having a particle size of less than 100µm, less than 80µm or less than 50µm. More preferably, the average particle size of the powdered material according to the invention ranges between 0.1µm and 100µm, between 1µm and 100µm or between 10µm and 100µm. The average particle size of the powdered material according to the invention ranges for example between 0.1µm and 80µm, between 0.1µm and 50µm, between 0.1µm and 30µm, between 0.1µm and 10µm or between 1µm and 10µm. The average particle size of the powdered material according to the invention is for example 3µm, 4µm or 5µm.

[0130] The particle size (average particle size) may be determined by any method known in the art. A preferred method for determining the particle size (average particle size) includes laser diffraction analysis.

[0131] Preferred powdered carrier materials comprise limestone fillers, such as limestone powder, mineral powders, for example sand or quartz powder, or combinations thereof.

[0132] In a preferred embodiment, the second component comprises at least one pH modifier. More preferably, the pH modifier or pH modifiers are present in an amount ranging between 0 and 6 wt % of the retarding cementitious binder of the first component.

[0133] Preferably, the at least one pH modifier comprises a hydroxide, such as calcium hydroxide Ca(OH)2, sodium hydroxide NaOH or potassium hydroxide KOH.

[0134] The second component may also comprise a binder material and / or an aggregate material and / or a supplementary cementitious material and / or one or more additional compounds.

[0135] The binder material comprises, for example, a cement-based binder material, an alkali-activated binder material, or a combination of a cement-based binder material and an alkali-activated binder material. Examples of cement-based binder materials and alkali-activated binder materials have been given above.

[0136] Aggregate materials include, for example, gravel, crushed stone or sand.

[0137] Supplementary cementitious materials (SCM) include, for example, fly ash, slag (blast furnace slag) and / or silica fume.

[0138] Additional compounds include, for example, plasticizers and / or superplasticizers.

[0139] In a first set of preferred embodiments, the second component comprises a carrier material, a cementitious binder material and at least one pH modifier. The cementitious binder present in the second component is preferably a cementitious binder other than the cementitious binder of the first component.

[0140] The pH modifier is preferably present in an amount between 0.1% and 6% by weight of the slow setting cementitious binder of the first component, for example, the pH modifier is present in an amount of 1%, 2%, 3%, 4% or 5% by weight of the slow setting cementitious binder of the first component. The second component of the first group of preferred embodiments may also include aggregate material and / or auxiliary cementitious material and / or one or more additional components, such as one or more plasticizers and / or one or more superplasticizers.

[0141] Preferred carrier materials include inert fillers, such as limestone or quartz powder. In other preferred embodiments, the carrier material includes a cement-based binder. Such a cement-based binder preferably has an initial setting time significantly greater than the initial setting time (T cem ). A preferred cement-based binder of the second component comprises Portland cement.

[0142] Obviously, carrier materials comprising inert fillers such as limestone or quartz powder and cement-based binders such as Portland cement are also conceivable.

[0143] Preferred pH modifiers include hydroxides such as calcium hydroxide Ca(OH)2, sodium hydroxide NaOH, and potassium hydroxide KOH.

[0144] The first and second streams preferably do not include salts of weak acids, such as carbonates (eg sodium carbonate or sodium bicarbonate), phosphates (eg sodium phosphate) and salts of carboxylic acids (eg salts of acetic acid, such as sodium acetate).

[0145] Specific examples of the first group of second components include:

[0146] - at least 30% by weight of inert fillers (such as limestone or quartz powder), between 0.1 and 6% by weight of calcium hydroxide or sodium hydroxide and aggregate material (sand);

[0147] - At least 20% by weight of inert filler, Portland cement, pH between 0.1 and 6% by weight of calcium hydroxide or sodium hydroxide and aggregate material (sand).

[0148] In a second group of preferred embodiments, the second component comprises a carrier material (eg, an inert filler) and an alkali-activated binder material.

[0149] In particular, the second component may include a combination of an alkali activated mixture (AAM) precursor and an alkali activated mixture (AAM) activator.

[0150] The alkali activated mixture precursor comprises, for example, fly ash, ground granulated blast furnace slag, copper slag, steel slag, metakaolin or blends thereof and mixtures thereof. The alkali activated mixture activator comprises, for example, hydroxide, silicate, sulfate or blends or mixtures thereof. Preferred alkali activated mixture activators comprise sodium hydroxide, sodium silicate, sodium sulfate and blends or mixtures thereof.

[0151] The second set of second components may also comprise aggregate material and / or one or more additional components, such as one or more plasticizers and / or one or more superplasticizers.

[0152] The second component is preferably mixed with water or an alkaline activation solution to provide the second stream.

[0153] The pH of the second stream is referred to as the second pH or pH 2. Preferably, the pH of the second stream (pH 2) is greater than the pH of the first stream (pH 1).

[0154] Preferably, the second pH (pH2) ranges between 10 and 14. The difference between the first pH and the second pH is 2 units, such as 2.5 units, 3 units or 4 units. In a preferred embodiment, the first pH is equal to 7 and the second pH is equal to 10. In an alternative embodiment, the first pH is equal to 8 and the second pH is equal to 11.

[0155] Aggregate materials include, for example, gravel and / or crushed stone and / or sand.Supplementary cementitious materials (SCM) include, for example, fly ash, slag (blast furnace slag) and / or silica fume.

[0156] In a preferred embodiment, the first component comprises sand as aggregate material.Preferably, the amount of sand is less than 60% by volume of the material of the first stream or less than 50% by volume of the material of the first stream.

[0157] In a preferred embodiment, the first component does not contain Portland cement.

[0158] The first component may also comprise one or more additional components, such as one or more plasticizers and / or superplasticizers.

[0159] The first component preferably comprises a flowable material.

[0160] In a preferred embodiment, the first component is mixed with water to provide a first stream.

[0161] The pH of the first stream is referred to as first pH or pH 1. Preferably, the pH of the first stream (pH 1) ranges between 7 and 10, and is for example equal to 7.5, 8, 8.5, 9 or 9.5.

[0162] The second component is preferably mixed with water or an alkaline activation solution to provide the second stream.

[0163] The pH of the second stream is referred to as the second pH or pH 2. Preferably, the pH of the second stream (pH 2) is greater than the pH of the first stream (pH 1).

[0164] Preferably, the second pH (pH2) ranges between 10 and 14. The difference between the first pH and the second pH is 2 units, such as 2.5 units, 3 units or 4 units. In a preferred embodiment, the first pH is equal to 7 and the second pH is equal to 10. In an alternative embodiment, the first pH is equal to 8 and the second pH is equal to 11. BRIEF DESCRIPTION OF THE DRAWINGS

[0166] The present invention is discussed in more detail below with reference to the accompanying drawings, in which:

[0167] - Figure 1 A system for extruding concrete according to the present invention is shown;

[0168] - Figure 2 A schematic diagram of the mixing process of the present invention is shown;

[0169] - Figure 3 shows a stress-strain diagram of Example 1 compared to a conventional 3D printable concrete mix;

[0170] - Figure 4 The penetration resistance of the mixtures according to the examples of the present invention compared with the comparative examples is shown.

[0171] Description of the implementation plan

[0172] The present invention will be described according to specific embodiments and with reference to certain drawings, but the invention is limited only by the claims and is not limited thereto. These drawings are only schematic and are not limiting. The dimensions of certain elements used for illustration in the drawings may be exaggerated and not drawn to scale. The dimensions and relative dimensions do not correspond to the actual practical reductions of the present invention.

[0173] When an endpoint of a range is mentioned, it includes the endpoint of the range.

[0174] In describing the present invention, unless otherwise stated, the terms used should be interpreted in accordance with the following definitions.

[0175] When two or more items are listed, the term "and / or" means that any one of the listed items can be used alone or two or more of the listed items can be used in any combination.

[0176] The terms "first", "second", etc. used in the specification and claims are used to distinguish similar elements and do not necessarily describe a sequence in time, space, order or in any other manner. It should be understood that the terms so used are interchangeable under appropriate circumstances.

[0177] The term "static mixer" refers to a device for continuously mixing fluid materials without the use of moving parts.

[0178] The term "dynamic mixer" refers to a device for continuously mixing fluid materials using moving parts.

[0179] The term "plasticizer" and the term "superplasticizer" refer to chemical additives in concrete that are used to (1) reduce the water / cement ratio and / or (2) prevent particle agglomeration of cement particles.

[0180] The term "retarder" refers to a chemical additive used to delay cement hydration and keep cement-based materials workable. Thus, the term "retarder" refers to a chemical additive that slows down the setting of cement-based materials and increases the initial setting time of cement-based materials.

[0181] The term "accelerator" refers to a chemical additive that, in contrast to a retarder, accelerates the hydration reaction of a cementitious material, thereby shortening the setting time of the cementitious material, especially the initial setting time of the cementitious material.

[0182] Figure 1 A system for extruding concrete according to the present invention is shown. The system includes a six-axis industrial robot with an articulated arm A. A first stream containing a slow-setting cement-based binder and water is pumped to a mixer D, such as a static or dynamic mixer, by a first pump B. A second stream containing a carrier material and water and having a pH higher than that of the first stream is pumped to the mixer D by a second pump C. The material of the first stream is mixed with the material of the second stream through the mixer D, and the mixture is extruded from the nozzle of the deposition head of the 3D printer to form a 3D printed object F. The first pump B, the second pump C and the extruder are controlled by a controller E. Concrete is placed by a robot arm A. The movement of the robot arm is controlled by a controller E. Once mixed by the mixer, the mixture should have sufficient fluidity to allow conveying and extrusion. On the other hand, the mixture should provide the required mechanical stability of the 3D printed object F.

[0183] Any type of mixer known in the art suitable for mixing the first and second flows is contemplated. Both static mixers and dynamic mixers are contemplated.

[0184] Any type of pump known in the art capable of pumping the first stream and / or the second stream may be considered. The pump is preferably capable of conveying high viscosity fluids at a stable flow rate. Alternatively, a positive displacement pump may be considered. In a positive displacement pump, the fluid is moved by capturing a fixed amount and pressing the captured volume into a discharge pipe. Examples of such pumps include progressive cavity pumps, peristaltic pumps, pulse pumps with multiple cavities, gear pumps, and screw pumps. Obviously, other types of pumps may also be considered.

[0185] Figure 2 The mixing process according to the method of the invention is shown.

[0186] Experimental Results

[0187] Example 1

[0188] In a first example, a first stream (mixture A) and a second stream (mixture B) were prepared using the following starting materials:

[0189] o Binder material: CSA cement. The specific gravity of CSA cement is 3.15. The chemical composition of CSA cement is given in Table 1;

[0190] o Borax (disodium tetraborate decahydrate, Na2B4O7·10H2O);

[0191] o Calcium hydroxide (CH) powder, from Carl Roth chemicals, analytical grade with purity greater than 96%;

[0192] oLimestone powder;

[0193] o Fine aggregate having a nominal maximum size of 2 mm, a fineness modulus of 2.4, and a specific gravity of 2.65.

[0194] The compositions of the first stream (Mixture A) and the second stream (Mixture B) are shown in Table 2. Mixture A and Mixture B were formulated according to the mixing schemes shown in Table 3 and Table 4, respectively.

[0195] Table 1. Chemical and mineralogical composition of CSA cement

[0196]

[0197] Table 2. Mixing ratios of Mix A (CSA cement-based mix) and limestone-based mix (Mix B) of Example 1 (kg / m 3 )

[0198]

[0199] Table 3. Mixing procedure for mixture A of Example 1

[0200]

[0201] rpm - revolutions per minute

[0202] Table 4. Mixing Procedure for Mixture B of Example 1

[0203]

[0204] rpm - revolutions per minute

[0205] Figure 3 Stress-strain diagrams of concrete deposited using Mix A and Mix B specified in Example 1 according to the method of the invention are shown, compared to concrete deposited using a mix for conventional 3D printing. Conventional mixes for 3D printing are single-component mixes that do not include accelerators. Conventional 3D printable mixes typically have an initial setting time in the range of 60 to 90 minutes.

[0206] from Figure 3 It can be clearly seen that the elastic modulus (slope of the stress-strain graph) and compressive strength (maximum stress from the stress-strain graph) of the 3D printable mix according to the present invention are significantly higher compared to typical conventional 3D printable concrete mixes.

[0207] Examples 2, 3 and 4

[0208] Examples 2, 3 and 4 comprising a first stream (mixture A) and a second stream (mixture B) are designated below using the following starting materials:

[0209] o Binder material (CSA cement), borax, calcium hydroxide (CH) powder, limestone powder, fine aggregate as specified in Example 1;

[0210] o Portland cement;

[0211] oSodium gluconate;

[0212] oAluminum sulfate;

[0213] o Superplasticizer (SP) polycarboxylate ether (MasterGlenium 51, from BASF);

[0214] o Alkali activated mixture (AAM) precursors comprising, for example, fly ash, blast furnace slag, metakaolin, steel slag or copper slag. Blends or mixtures of these materials are also contemplated;

[0215] o Alkali activated mixture (AAM) activators, which contain, for example, sodium hydroxide, sodium silicate, or sodium sulfate. Blends or mixtures of these materials are also contemplated.

[0216] The compositions of the first stream (mixture A) and the second stream (mixture B) of Examples 2, 3 and 4 are given in Table 5 (Example 2), Table 6 (Example 3) and Table 7 (Example 4).

[0217] Table 5. Mixing ratio of mixture A (CSA cement-based mixture) and mixture B (Portland cement-based mixture) of Example 2 (kg / m 3 ).

[0218]

[0219] Table 6. Mixing ratios of Mix A (CSA cement-based mix) and Mix B (Portland cement-based mix with calcium hydroxide) of Example 3 (kg / m 3 )

[0220]

[0221] Table 7. Mixing ratios (kg / m) of mixture A (CSA cement-based mixture) and mixture B (alkali-activated mixture) according to the fourth embodiment of the present invention 3 )

[0222]

[0223] AAM—Alkali Activated Material

[0224] Examples 5, 6, 7 and 8

[0225] The setting time of the concrete obtained according to the invention was compared with that of the comparative example.

[0226] In Examples 5 to 8, two different mixtures (mixture A1 and mixture A2) were used as the first stream, and two different mixtures (mixture B1 and mixture B2) were used as the second stream. The combined mixtures are shown in Table 9. The compositions of mixtures A1, A2, B1, B2 are shown in Table 10. The pH of mixtures B1 and B2 are given in Table 10.

[0227] In Examples 5 to 8, the volume ratio of the first stream (mixture A1 or A2) to the second stream (mixture B1 or 2) is 70:30.

[0228] Table 9. Combinations of Mixtures A and B

[0229]

[0230] Table 10. Mixing ratios of mixtures A1, A2, B1 and B2

[0231]

[0232] The initial setting time and the final setting time of the mixtures given in Examples 5 to 8 were measured using a penetration test, wherein the initial and final setting times were determined as the times when the penetration resistance was equal to 3.5 MPa and 27.6 MPa. Figure 4 The penetration resistance of the mixtures of Examples 5, 6, 7 and 8 is shown, where Mix 1 represents Example 5, Mix 2 represents Example 6, Mix 3 represents Example 7, and Mix 4 represents Example 8.

[0233] Figure 4 It is clearly shown that when A2 (first stream) and mixture B1 (second stream) ( Figure 4 The "surprising effect" of the combination of mixture 2) is expressed as Figure 4 The mixture of this combination exhibits a very low initial setting time compared to the other combinations shown in. The initial setting time T3 of the combined mixture of mixture A2 and mixture B1 is less than 5 minutes.

Claims

1. A method for depositing concrete layer by layer, the method comprising providing an extrudable concrete by: - feeding the first and second streams to a mixer, The first stream has a first pH (pH 1) and comprises a first material and optionally water, the first material comprising a retarded cementitious binder obtainable by mixing a cementitious binder with a retarder, the cementitious binder having an initial setting time T cem The slow-setting cement-based adhesive has an initial setting time T ret cem , wherein the cementitious binder is selected from the group consisting of calcium sulfoaluminate and calcium aluminate, wherein the retarder comprises a compound that, when mixed with the cementitious binder to provide the retarded cementitious binder, is capable of affecting the initial setting time, such that the initial setting time T of the retarded cementitious binder is ret cem Higher than the initial setting time T of the cement-based adhesive cem , and wherein the retarder is capable of influencing the pH of the first stream such that the first pH (pH1) of the first stream is lower than a pH of a stream that is equal to the first stream but comprises the cementitious binder instead of the retarding cementitious binder and does not comprise the retarder, the retarder comprising a compound comprising boron and sodium; The second stream has a second pH (pH2) and comprises a second material and optionally water, the second material having a second initial coagulation time (T2), wherein the second pH (pH2) is greater than the first pH (pH1) and wherein the difference between the first pH (pH1) and the second pH (pH2) is at least 2, the second material comprises a support material and optionally a pH modifier, wherein the volume fraction of the support material is at least 20% by volume of the second stream; - mixing the first stream and the second stream in the mixer to obtain a third stream comprising an extrudable concrete, the third stream comprising a mixture of the first material, the second material and optionally water, wherein the mixture of the first material and the second material has an initial setting time T3, whereby the initial setting time T3 is less than the initial setting time T3 of the slow setting cement-based binder ret cem .

2. The method according to claim 1, wherein the second material comprises a cementitious binder and a pH modifier and optionally a binder material and / or an aggregate material and / or a supplementary cementitious material and / or one or more additional compounds.

3. The method according to claim 1 or claim 2, wherein the initial setting time T3 is less than the initial setting time T3 of the cement-based adhesive. cem .

4. The method according to any one of the preceding claims, wherein the first pH (pH1) ranges between 7 and 10, and the second pH (pH2) ranges between 10 and 14.

5. The method of any one of the preceding claims, wherein the retarder comprises disodium tetraborate decahydrate.

6. A method according to any one of the preceding claims, wherein the volume fraction of the support material is at least 20% by volume of the second material.

7. The method according to any one of the preceding claims, wherein the second material comprises at least 20% by volume of pulverulent carrier material having an average particle size of less than 100 μm.

8. The method of claim 7, wherein the powdered carrier material comprises limestone powder, mineral powder, or a combination thereof.

9. The method according to any one of the preceding claims, wherein the pH modifier comprises a hydroxide.

10. The method according to any one of the preceding claims, wherein the binder material comprises a cementitious binder material, an alkali-activated binder material or a combination of a cementitious binder material and an alkali-activated binder material, and / or wherein the at least one additional compound comprises a plasticizer or a superplasticizer.

11. The method according to any one of the preceding claims, wherein both the first stream and the second stream are free of carbonates and sulfates.

12. A two-component cementitious binder composition comprising a first component and a second component, wherein the first component comprises a retarding cementitious binder obtainable by mixing at least 30 wt. % of a first cementitious binder selected from the group consisting of sulphoaluminate cement, aluminate cement and combinations thereof, between 0.1 and 5 wt. % of a retarder, the first cementitious binder being selected from the group consisting of sulphoaluminate cement, aluminate cement and combinations thereof, the retarder comprising a compound containing boron and sodium, And wherein the second component comprises a support material and an optional pH modifier, wherein the volume fraction of the support material is at least 20 volume % of the second component.

13. The two-component cementitious adhesive composition of claim 14, wherein the second component further comprises a pH modifier, the pH modifier being present in an amount ranging between 0 and 6 wt% of the slow setting cementitious adhesive of the first component.

14. A two-component cementitious adhesive composition according to claim 12 or claim 13, wherein the pH modifier comprises a hydroxide.

15. A two-component cementitious binder composition according to any one of claims 12 to 14, wherein the second component further comprises a binder material and / or an aggregate material and / or a supplementary cementitious material and / or one or more additional compounds.

16. A two-component cementitious binder composition according to any one of claims 12 to 15, wherein the binder material of the second component comprises a cementitious binder material and the second component comprises at least one pH modifier, wherein the binder material of the second component comprises an alkali-activated binder material.

Citation Information

Patent Citations

  • Method for layer-by-layer deposition of concrete

    WO2021214239A1